ASSESSMENT OF CHINTENI RIVULET (ROMANIA) WATER QUALITY UNDER THE IMPACT OF THE ANTHROPOGENIC FACTOR - MARTONOȘ, Ildiko Melinda; PETRUȘ, Maria; ROȘU, Cristina (Studia Universitatis Babeș-Bolyai Ambientum, 2018)
In the environmental issue context, surface water quality has an important place. Implementing measures truly effective, sustainable in prevention and control of water pollution, is urgently needed, because degradation of their quality affects the quality of human life. This paper presents the study and research on the assessment of quality status of Chinteni Rivulet (Cluj County) under the pressure created by possible anthropogenic pollution sources. Water sampling was conducted in the period November 2015 - May 2016, in five representative points. We measured the physico-chemical parameters (pH, temperature, total dissolved solids, electrical conductivity, redox potential, chlorides, sulfates, nitrates, nitrites, ammonium, filterable residue dried at 105 °C, suspended matter and total chromium) and oxygen regime parameters (dissolved oxygen, chemical oxygen demand). Results show that there were registered high contents of nitrates, nitrites, sulfates, oxidisable organic substances, chlorides and total chromium, downstream from the anthropogenic sources of pollution. The anthropogenic sources of pollution put pressure on the water quality of Chinteni rivulet, and the trend is of the increase of pollutants and is directly proportional to the population density and intensification of economic activities.